2013
DOI: 10.1371/journal.pone.0081155
|View full text |Cite
|
Sign up to set email alerts
|

Epitopes of Microbial and Human Heat Shock Protein 60 and Their Recognition in Myalgic Encephalomyelitis

Abstract: Myalgic encephalomyelitis (ME, also called Chronic Fatigue Syndrome), a common disease with chronic fatigability, cognitive dysfunction and myalgia of unknown etiology, often starts with an infection. The chaperonin human heat shock protein 60 (HSP60) occurs in mitochondria and in bacteria, is highly conserved, antigenic and a major autoantigen. The anti-HSP60 humoral (IgG and IgM) immune response was studied in 69 ME patients and 76 blood donors (BD) (the Training set) with recombinant human and E coli HSP60,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 88 publications
0
41
0
1
Order By: Relevance
“…This is pertinent given that HSP production appears to be deficient in CFS patients, and the HSPs produced appear to be dysfunctional, which could potentially provide another mechanism underpinning a prolonged and/or exaggerated immune response to pathogen invasion and other sources of inflammation such as stress, medical comorbidity and lifestyle factors in such patients (Elfaitouri et al 2013; Jammes et al 2005, 2009, 2011, 2012). …”
Section: Acute Infection and The Development Of Chronic Iandons: The Romentioning
confidence: 99%
“…This is pertinent given that HSP production appears to be deficient in CFS patients, and the HSPs produced appear to be dysfunctional, which could potentially provide another mechanism underpinning a prolonged and/or exaggerated immune response to pathogen invasion and other sources of inflammation such as stress, medical comorbidity and lifestyle factors in such patients (Elfaitouri et al 2013; Jammes et al 2005, 2009, 2011, 2012). …”
Section: Acute Infection and The Development Of Chronic Iandons: The Romentioning
confidence: 99%
“…Hypothetically, dangerassociated molecular patterns (DAMPs), such as mitochondrial DNA (mtDNA), heat shock proteins (Hsps), and cardiolipins could be released from the mitochondria (41)(42)(43) in ME/CFS and act as autoantigens. We previously found that a subset of ME/CFS patients had higher levels of IgM antibodies against epitopes of both mitochondrial and bacterial Hsp-60 (despite the absence of an infectious pathogen) which potentially may lead to dysfunctional mitochondria (11). Our hypothesis on the presence of autoantibodies against cardiolipin in ME/CFS patients was based on previous publications (ref in Table 1), could not be confirmed here, possible explained by different inclusion and exclusion criteria of patients in previous studies that did not used Canadian criteria, but included leukemia/lymphoma and type 1 diabetes patients.…”
Section: Discussionmentioning
confidence: 99%
“…Intermediate filaments (8) Phosphatidylserine (4) Phospholipids, gangliosides (5) Mitochondria Heat shock protein 60 (11) Cardiolipin (4,12,13) Neo-antigens Oleic acid (14) Palmitic acid, myristic acid, S-farnesyl-L-cysteine, malondialdehyde, azelaic acid (15) NO-tyrosine (14,15) NO-phenylalanine (14,15) NO-arginine, NO-tryptophan, NO-cysteinyl (14) NO-Bovine serum albumin (16) NO-histidine, NO-creatine, NO-asparagine (15) Other targets dUTPase (17) Endothelial cells, neuronal cells (4) NO-, nitrosylated; dUTPase, deoxyuridine 5 ′ -triphosphate nucleotide hydrolase.…”
Section: Introductionmentioning
confidence: 99%
“…Immunoassay (SMIA) ( Figure 2) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. We have used it for research on diagnosis and seroprevalence.…”
Section: In My Group We Have Developed a Multiplex Serological Technmentioning
confidence: 99%